BIMTEK PENGELOLAAN KEUANGAN BERBASIS GOOD CORPORATE GOVERNANCE DAN PAJAK PADA BUMDES KARYA MANDIRI DESA CIBODAS-LEMBANG - Said, Lina; Devi Anna, Yane (Universitas PGRI Yogyakarta, 2023)
With the granting of village autonomy, villages can take advantage of opportunities by developing and maximizing the potential of their villages by establishing Village-Owned Enterprises (BUMDes). The establishment of BUMDes Karya Mandiri in Cibodas Village-Lembang was motivated by the need for clean water and the discovery of springs that could be used for the needs of the villagers. Along with the development of the Karya Mandiri BUMDes business unit, it is not only clean water management but also increased by the presence of Village Kiosks, waste management, multi-purpose building rentals and package delivery in collaboration with Shopee. The problems faced by BUMDes Karya Mandiri are financial management and understanding of BUMDes taxes that need improvement. The method used in the service begins with conducting a survey to identify the problem. The next stage is providing training, solutions are given according to the problem, among others related to financial management with control based on the implementation of good corporate governance and taxation for BUMDes, then assistance on improvement and monitoring implementation. Keywords: BUMDes, Finance, GCG, Tax.